Knowledge Management Factors Affecting Construction Project Performance Model - Eman Mohammed Abdulrahman Alhammadi; Sonia Lohana (International Journal of Sustainable Construction Engineering and Technology, 2022)
This paper presents the development of knowledge management factors affecting to construction project performance model of UAE construction company. The data used to develop the model was collected from questionnaire survey on large construction company in UAE. The respondents were the employees of the construction company that were requested to gauge each of the knowledge management factors using 5-points Likert scale that they perceived affecting the company performance.  A total of 291 valid responses were used for this analysis. After the model was constructed, it was evaluated at the measurement component of the model where it involved examining the indicator reliability, convergent validity, and discriminant validity. Then at structural component, it involved checking the strength of the relationship, checking coefficient of determination, conduct predictive relevance of the model, calculate goodness-of-fit (GOF) and conduct hypotheses testing. It was found that two out of four constructs are significant which are having t-value above the cut-off value of 1.96. The significant relationships are knowledge management technology (KMT) and knowledge management process (KMP) toward project performance. These outcomes are from actual perception from the respondents where the collected data is not strong enough to trigger the significant relationship of other constructs that had been hypothesised. The model can help to give better understand to parties that concerned the knowledge management in construction industry.